THE EFFORTS TO ENHANCE MATHEMATICS ACTIVITY USING PROBLEM-POSING APPROACH IN STUDENTS CLASS VIII - Aisyah Nur Istiqomah; Abdul Taram (Universitas Ahmad Dahlan, 2018)
A less exciting approach to mathematics learning makes student activity in deep mathematics learning. This research aims to increase the learning activities of mathematics by using the problem-posing approach of students of class VIII C Odd Semester Muhammadiyah Junior High School 1 Godean (SMP Muhammadiyah I Godean) Sleman District Academic Year 2017/2018. This study is a Classroom Action Research with the subject of research class VIII C SMP Muhammadiyah I Godean. The object in this study is the learning activities of mathematics students after learning mathematics with a problem-posing approach. The study was conducted in two cycles, each cycle consisting of two face-to-face. The technique of collecting data using observation. Data analysis used qualitative descriptive analysis. This research shows that the problem-posing approach can increase the learning activity of mathematics of VIII C students of SMP Muhammadiyah I Godean of Sleman Regency in odd semester of the academic year 2017/2018. This is evident from the average percentage of analysis results observation sheet activity of students cycle I is 55.60%. The student activity qualifications insufficient criteria, and on the second cycle average percentage analysis results observation sheet student activity increased to 70.05%, then the qualification student activity in good criteria. These results indicate that an increase in student learning activities is quite significant. The results of this study indicate an increase in activity during mathematics learning on the subject of Algebraic.